Correlations between Total Antioxidant Capacity and 8-Hydroxydeoxyguanosine with Carotid-Femoral Pulse Wave Velocity in Chronic Kidney Disease - Mochammad Yusuf Alsagaff; Budi Susetyo Pikir; Mochammad Thaha; Hendri Susilo (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Chronic kidney disease (CKD) is often associated with an increased risk of cardiovascular disease. Cardiovascular disease in CKD can be affected by oxidative stress and inflammation. The oxidative stress can affect arterial stiffness, especially in patients with CKD, which will increase the risk of cardiovascular disease. This study aimed to explain the correlation between total antioxidant capacity (TAC) and 8-hydroxydeoxyguanosine (8-OHdG) with carotid-femoral pulse wave velocity (cf-PWV) in patients with CKD.METHODS: Forty-three CKD patients was included in this cross-sectional study. TAC was measured from serum samples by colorimetric method and 8-OHDG was measured from urine by enzyme-linked immunoassay method. cf-PWV was measured by Doppler ultrasound as a diagnostic tool for arterial stiffness.RESULTS: Significant correlations were found between age, estimated glomerular filtration rate (e-GFR), Hemoglobin A1C (HbA1C), serum creatinine, cystatin-C, and severity of CKD with urinary 8-OHdG levels. Serum creatinine, cystatin-C, severity of CKD, age, high-density lipoprotein (HDL), e-GFR, and HbA1C also had significant correlations with serum TAC levels. Other significant correlations between e-GFR, HbA1C, serum creatinine, cystatin-C, and severity of CKD with cf-PWV were also obtained. A significant negative correlation was obtained between serum TAC and cf-PWV with moderate levels of correlation coefficient (r=-0.504).CONCLUSION: There was a negative correlation between TAC and cf-PWV, but there was no significant correlation between 8-OHdG and cf-PWV in patients with CKD.KEYWORDS: chronic kidney disease, total antioxidant capacity, 8-hydroxydeoxyguanosine, carotid-femoral pulse wave velocity